Study on Deformation and Fracture Evolution of Underground Reservoir Coal Pillar Dam under Different Mining Conditions. (30th March 2022) - Xuesheng, Liu; Shilin, Song; Baoyang, Wu; Xuebin, Li; Kang, Yang
Abstract : Coal mine underground reservoir water storage technology is an effective technical way to achieve high efficiency of coal mining and protection of water resources. The stability of coal pillar dam plays a decisive role in the safe and stable operation of underground reservoirs. Mining of adjacent working faces and long-term water erosion are the main influencing factors of stability of coal pillar dam. In this paper, a fluid-solid coupling calculation model for the deformation and evolution of coal pillar dam was established by FLAC3D numerical simulation software and the underground brine reservoir of Lingxin Coal Mine of Shenning group as an engineering background. The paper studied systematically the deformation, failure, and stress evolution of the dam with coal pillars soaked in water for a long time under different working face inclining length, coal pillar width, mining height, and water pressure. The simulation results showed that the degree of deformation and failure of the coal pillar dam continued to increase with the continuous advancement of the working face. The plastic zone of the coal pillar dam was increased by approximately 23.53%, the maximum vertical stress was increased by approximately 95.78%, and the maximum vertical deformation was increased by approximately 68.18%. The influence of each factor on the deformation and failure of overburden strata is quite different. The development range of plastic zone, the maximum vertical stress, and the maximum vertical deformation were increasing with the increased of working face inclined length and mining height. The increasing width of coal pillar would lead to the decrease of maximum vertical stress. The increase of water pressure would lead to the decrease of maximum vertical deformation. It can be seen that the inclined length of the working face is the main factor affecting the deformation and failure of the coal pillar dam. Coal pillar width and mining height are the main factors affecting the development of plastic zone. This study reveals the law of deformation and fracture evolution of coal pillar dam under different mining conditions, which can provide a reference for the design of coal pillar dam of coal mine underground reservoir.